SENSIBILITY OF THE PLANETARY BOUNDARY LAYER PARAMETERIZATIONS BY WRF SINGLE-COLUMN MODEL IN THE ALCANTARA LAUNCH CENTER - Ramos, Diogo Nunes da Silva (2016)
This study evaluates the planetary boundary layer (PBL) by the sensitivity of different PBL parameterizations for the Alcântara Rocket Launch Center (CLA). The study was produced using two distinct databases, an observational and other numeric. The observational data in surface and radiosondes were of the CHUVA Project for the Alcantara campaign and applied in comparison with the WRF-SCM integrations. These integrations were obtained using five PBL parameterizations (YSU, MYJ, QNSE, MYNN2 and TEMF) in the WRF model (3.7.1) in its version of Single-Column Model (SCM), with initial condition of NCEP’s global model final analysis (FNL/GFS) for 18Z on March 5, 2010, integrating for 30 hours simulations considering spin-up (6 + 24 hours). The overall results do not highlight a standardization of quality of some parameter, despite the MYNN, QNSE and YSU schemes have been closer to the observations at different situations. The PBL height determination was better simulated with YSU and QNSE schemes, and with MYJ to air temperature at 2m. Importantly, the dynamic limitations that an SCM model has also adding the complexity of the Alcântara site and its coastal features of meso and large scale (eg breezes and ITCZ). These problems motivates the future studies, for example, with three-dimensional microscale models such as LES.